Auditory scene reproduction for tele-operated robot systems. (18th April 2019) - Liu, Chaoran; Ishi, Carlos; Ishiguro, Hiroshi
ABSTRACT: In a tele-operated robot environment, reproducing auditory scenes and conveying 3D spatial information of sound sources are inevitable in order to make operators feel more realistic tele-presence. In this paper, we propose a tele-presence robot system that enables reproduction and manipulation of auditory scenes. This tele-presence system is carried out on the basis of 3D information about where targeted humans are speaking, and matching with the operator's head orientation. We employed multiple microphone arrays and human tracking technologies to localize and separate voices around a robot. In the operator site, separated sound sources are rendered using head-related transfer functions (HRTF) according to the sound sources' spatial positions and the operator's head orientation that is being tracked real time. Two-party and three-party interaction experiments indicated that the proposed system has significantly higher accuracy when perceiving direction of sounds and gains higher subjective scores in sense of presence and listenability, compared to a baseline system which uses stereo binaural sounds obtained by two microphones mounted on the humanoid robot's ears. GRAPHICAL ABSTRACT: